Problem-Based Learning in Biology Learning: Implementation in PPG Students of Manado State University - Naharia, Orbanus (International Journal of Information Technology and Education, 2024)
This study aims to assess the effects of incorporating the Problem-Based Learning (PBL) approach on the acquisition of biology knowledge among PPG students at Manado State University. The research subject comprised 31 students, comprising 14 males and 17 females. This is an instance of educational research referred to as classroom action research, which especially adheres to the approach defined by Kemmis and Taggart. The research was carried out in two distinct phases: the initial phase encompassed planning, execution, action, and observation, while the subsequent phase centered on reflection. Data for the research was gathered by conducting assessments that included both multiple-choice and essay questions. Professionals evaluate Psychomotor learning outcomes through direct observation utilizing a psychomotor assessment form. The cognitive outcomes of cycle I were 51.61% and the cognitive outcomes of cycle II were 80.64%. The psychomotor learning outcomes related to tool and material preparation showed a 19.35% rise, whereas the outcomes for tool and material assembly demonstrated a 25.80% increase. The experimental component experienced a 22.58% increase, the observational component saw a 29.03% increase, and the delivery part of the trial witnessed a significant 41.93% increase. Research indicates that implementing Problem-Based Learning (PBL) can enhance students’ academic achievement.